2019
DOI: 10.1021/acsphotonics.9b00636
|View full text |Cite
|
Sign up to set email alerts
|

Disordered and Densely Packed ITO Nanorods as an Excellent Lithography-Free Optical Solar Reflector Metasurface

Abstract: Precise control and stabilization of the operating temperature environment of spacecraft and satellites during their life cycle is of paramount importance to increase device reliabilities and reduce the thermomechanical constraints. Optical solar reflectors are the physical interface between the spacecraft and space, and they are broadband mirrors for the solar spectrum, while having strong thermal emission in the mid-infrared part of the electromagnetic spectrum. Strong light−matter interactions in metamateri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 90 publications
0
40
0
Order By: Relevance
“…Assembling in a suitable way layers with adequate (natural or effective) wavelength‐dependent dielectric functions is also useful to design planar structures with functionalities requiring multispectrally‐tuned optical properties. As a first example, nanostructured columnar ITO nanofilms with tailored effective optical properties were used to build ITO/dielectric/Ag mirror cavities with a high reflectance in the solar spectrum and a high absorbance and emissivity at longer wavelengths in the infrared . Such cavities can be useful to design solar reflectors with efficient radiative cooling properties.…”
Section: Film Interferencementioning
confidence: 99%
“…Assembling in a suitable way layers with adequate (natural or effective) wavelength‐dependent dielectric functions is also useful to design planar structures with functionalities requiring multispectrally‐tuned optical properties. As a first example, nanostructured columnar ITO nanofilms with tailored effective optical properties were used to build ITO/dielectric/Ag mirror cavities with a high reflectance in the solar spectrum and a high absorbance and emissivity at longer wavelengths in the infrared . Such cavities can be useful to design solar reflectors with efficient radiative cooling properties.…”
Section: Film Interferencementioning
confidence: 99%
“…Moreover, the simultaneous formation of small and large particles could excite both FP and LSPR modes to achieve both semiconductor light absorption enhancement and plasmonic hot electron injection. In recent studies, we developed a facial route based on oblique angle deposition to synthesize plasmonic nanostructures on a large scale. Moreover, we demonstrated that as a result of the cyanide chemistry, so‐called CoFe‐Prussian blue analog (PBA) is a strong and robust water oxidation catalyst (WOC), when connected to an organic chromophore .…”
Section: Introductionmentioning
confidence: 99%
“…This is beneficial for the conventional metamaterial applications where a well‐defined absorption band is required, for example, for biochemical sensing applications or tailored thermal emission. TCOs are, due to their high losses and consequently their larger resonances, more adapted for broadband absorption and find their application, for example, as optical solar reflectors for thermal control of spacecraft and satellites, where they benefit moreover from their resistance to harsh environments …”
Section: Introductionmentioning
confidence: 99%